The Effect of 7P Marketing Mix on Purchasing Decisions and Repurchases at Mixue Sidoarjo Consumers - Santoso, Sri Nadine; Waluyo, Minto (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
Along with the increase in population, the level of consumption of food and beverages in society is also increasing, one of which is ice cream. Mixue ice cream & tea is one of the franchises that offers ice cream products and various other drinks that are currently on the rise or popular among the public. To ascertain how the 7p marketing mix affects consumers' decisions to buy and repurchase products, researchers aim to study Mixue Sidoarjo consumers. Respondents in this study were 130 consumers of Mixue Sidoarjo. Data analysis was carried out using the SEM method where the results of the SEM were followed by strengthening the SWOT analysis matrix as a proposed strategy in increasing consumer growth in making repeat purchases. The results showed that product, price, people, and place had a positive and significant effect on purchasing decisions. Meanwhile, promotion and process have a negative and insignificant effect on purchasing decisions. Purchasing decisions have a positive and significant effect on repeat purchases. The simultaneous equation for purchasing decisions is Y1 = 1,045X1 + 0,566X2 – 1,256X3 – 0,426X4 + 0,252X5 + 1,347X6 + Z7and the simultaneous equation for repurchase is 0,892X1 + 0,483X2 – 1,073X3 – 0,364X4 + 0,215X5 + 1,15X6 + Z8. In strengthening the SWOT analysis by compiling a SWOT matrix, there are four types of alternative strategies that can be applied by Mixue Sidoarjo. In terms of business conditions, the strategy that can be applied is the W-T strategy which utilizes the weakness and threats factors of Mixue Sidoarjo.